Investigating the Appropriateness of Admission and Hospitalization at a Teaching Hospital: A Case of a Developing Country - Mahmood NEKOEI MOGHADAM; Mohammadreza AMIRESMAILI; Reza GOUDARZI; Saeed AMINI; Sajad KHOSRAVI (Tehran University of Medical Sciences, 2017)
Background: Reduction of inappropriate use of health services can decrease health care costs without harming the quality of services. This study aimed to investigate inappropriate admission and hospitalization at Afzalipour Hospital of Kerman, Iran. Methods: Inappropriate admission and hospitalization were assessed via a cross-sectional study on 400 patients in Kerman Afzalipour Hospital, Kerman, Iran in 2015. The Iranian version of the Appropriateness Assessment Protocol was used for data collection. Chi-square tests and logistic regression were used to analyze the data. Results: The rate of inappropriate admissions and hospitalization were 7.6% and 9% respectively. There was no significant relationship between inappropriate admissions and any of the studied variables; however, there was a significant relationship between inappropriate hospitalization and age, length of stay and hospital departments. Conclusion: If standard measures of admission and hospitalization execute correctly, unnecessary hospitalization rate can be reduced, so more patients can be treated and cost and workload of hospital personnel can be moderated.